2023
DOI: 10.1002/tpg2.20369
|View full text |Cite
|
Sign up to set email alerts
|

Use of genomic prediction to screen sorghum B‐lines in hybrid testcrosses

Abstract: Use of trifluoromethanesulfonamide (TFMSA), a male gametocide, increases the opportunities to identify promising B‐lines because large quantities of F1 seed can be generated prior to the laborious task of B‐line sterilization. Combining TFMSA technology with genomic selection could efficiently evaluate sorghum B‐lines in hybrid combination to maximize the rates of genetic gain of the crop. This study used two recombinant inbred B‐line populations, consisting of 217 lines, which were testcrossed to two R‐lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
2
3
0
Order By: Relevance
“…The prediction accuracies for days to mid-anthesis and grain yield ( Figure 4 ) are like those reported in other studies in sorghum [ 5 , 15 , 16 , 20 , 21 , 22 , 23 ]. However, the prediction accuracies for plant height are lower than in previous studies, much like what was observed by Winans et al [ 5 ] and Sapkota et al [ 22 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The prediction accuracies for days to mid-anthesis and grain yield ( Figure 4 ) are like those reported in other studies in sorghum [ 5 , 15 , 16 , 20 , 21 , 22 , 23 ]. However, the prediction accuracies for plant height are lower than in previous studies, much like what was observed by Winans et al [ 5 ] and Sapkota et al [ 22 ].…”
Section: Discussionsupporting
confidence: 85%
“…Modest increases in prediction accuracy do not always translate into large gains in selection efficiency [ 5 , 20 ]; however, it may also be beneficial to expend effort to create more robust training sets for a few reasons. One major goal of the GUESS program was to introgress novel genetic diversity into sorghum without sacrificing the agronomic performance of the resulting lines.…”
Section: Discussionmentioning
confidence: 99%
“…The BTx623/BTx642 population had a wider range of genetic variation than the BTx623/BTx378 population. Similar results are reported in Kent et al (2023) using a smaller set of these lines that were evaluated in hybrid test crosses.…”
Section: Genetic Distancesupporting
confidence: 83%
“…This would also explain why the prediction accuracies for PH did not improve when the populations were combined. When a select number of lines from these two populations in hybrid test crosses for grain yield and DY were assessed (Kent et al, 2023 ), it was observed that combining the two populations improved in some scenarios. Similarly, literature has shown both moderate increases and decreases in prediction accuracy when populations are combined (Brandariz & Bernardo, 2019;Haile et al, 2021;Heffner et al, 2011).…”
Section: Crop Sciencementioning
confidence: 99%
See 1 more Smart Citation